How safe is eating chicken? - Romano, Donato (Proceedings e report, 2006)
Consumers trust is a key factor in dealing with rising concerns about food safety and food quality, but only few studies have dealt with consumer attitudes and none of them has tried to model the process of consumer response. This book reports the main findings of an european project aimed at analysing trust along the food chain and its relationship with food risk communication. The papers collected investigate the mechanisms that determine the social diffusion of trust, examining the interplay of the psychological, sociological and economic factors; and analyze the impact of the food risk communication policies on consumers and producers and on the society as a whole.